Early Breeding Conditions Followed by Reduced Breeding Success Despite Timely Arrival in an Alpine Migratory Songbird - Sander, Martha Maria; Chamberlain, Dan; Mermillon, Camille; Alba, Riccardo; Jähnig, Susanne; Rosselli, Domenico; Meier, Christoph Manuel; Lisovski, Simeon (Frontiers in Ecology and Evolution, 2021)
Timing reproduction to coincide with optimal environmental conditions is key for many organisms living in seasonal habitats. Advance in the onset of spring is a particular challenge to migratory birds that must time their arrival without knowing the conditions on the breeding grounds. This is amplified at high elevations where resource availability, which is linked to snowmelt and vegetation development, shows much annual variation. With the aim of exploring the effects of variability in the onset of local resource availability on reproduction, we compared key life history events in an Alpine population of the Northern Wheatear (Oenanthe oenanthe) between years of contrasting timing of snowmelt. Based on remote sensed images, we identified 2020 as an exceptionally early snowmelt and green-up year compared to the preceding year and the long-term average. Individuals tracked with light-level geolocators arrived well before the snowmelt in 2020 and clutch initiation dates across the population were earlier in 2020 compared to 2019. However, observations from a citizen science database and nest monitoring data showed that the arrival-breeding interval was shorter in 2020, thus the advance in timing lagged behind the environmental conditions. While hatching success was similar in both years, fledging success was significantly reduced in 2020. A trophic mismatch in early 2020 could be a possible explanation for the reduced reproductive success, but alternative explanations cannot be excluded. Our results show that, despite the timely arrival at the breeding grounds and a contraction of the arrival-breeding interval, Wheatears were not able to advance breeding activities in synchrony with environmental conditions in 2020. Earlier reproductive seasons are expected to become more frequent in the future. We show that the negative effects of changing seasons in Alpine migratory birds might be similar to birds breeding at high latitudes, despite their shorter migratory distance.